An Analysis of Violations of The Theory of Maxims of Quality in Speech at Bocah-Bocah Kosong (BBK) x Indy Barends - Dina Wulansari; Syihabuddin Syihabuddin; Mahardhika Zifana (Journal of Pragmatics Research, 2026)
This study aims to examine violations of the Maxim of Quality in discussions featured on the YouTube program Bocah-Bocah Kosong X Indy Barends based on Grice’s Maxim Theory (1975). The analysis focuses on utterances that lack evidential support and those that are hyperbolic, metaphorical, imaginative, or fantastical in nature. Adopting a qualitative pragmatic approach, the data were analyzed through content analysis, supported by the calculation of intercoder reliability using Krippendorff’s alpha and multimodal triangulation. The findings reveal that the most dominant forms of violation are hyperbolic humor (38%), absurd metaphors (22%), false identity claims (18%), and supernatural or fantasy-related statements (12%). These results indicate that violations of the Maxim of Quality do not merely represent communicative errors; rather, they function as performative strategies employed by Generation Z to construct humor, social solidarity, and creative, imaginative speaker identities within digital spaces. Theoretically, this study contributes to contemporary pragmatic scholarship by positioning maxim violations as meaningful communicative practices in digital culture. Nevertheless, the study is limited by the narrow scope of data, which is confined to a single episode with a relatively small number of utterances, as well as by the potential for performativity bias due to the entertainment-oriented nature of the content. Accordingly, future research is recommended to expand the data corpus, compare diverse contexts of Generation Z digital communication, and develop cross-maxim analyses of Grice’s framework in order to achieve a more comprehensive understanding of the pragmatic strategies of the digital generation.